The Influence of Self Esteem and Work Ethic on Organizational Commitment of Civil Servants Marine and Fisheries Service West Kalimantan Province - Muhammad Wahyu Riadi; Devi Yasmin; Irfan Mahdi (UM Purwokerto Press, 2024)
This research aims to determine the influence of Self Esteem and work ethic on the organizational commitment of Civil Servants of the Maritime and Fisheries Service of West Kalimantan Province. The data analysis method in this research is multiple linear regression analysis, correlation coefficient (R), coefficient of determination (R2), simultaneous test (F test) and partial test (t test). The value of the multiple linear regression equation obtained is Y = 2.651 + 0.243X1 + 0.667X2. This means that if Self Esteem and work ethic are worth 0 then the organizational commitment of Civil Servants at the Maritime and Fisheries Service of West Kalimantan Province is worth 2,651 units. The correlation coefficient value is 0.607. Thus, it can be interpreted that the relationship between independent variable and dependent variable is categorized as strong. The coefficient of determination is 0.369 or equal to 36.9%. Thus the Self Esteem and work ethic influence the organizational commitment variable by 36.9%. The results of the simultaneous test (F Test) are Fcount value 16.364 < Ftable 2.712. This means that Self Esteem and Work Ethic together influence the Organizational Commitment. The results of the partial test (t test) on the Self Esteem variable (X1) are tcount value is 2.519 > ttable 1.987, meaning that the Self Esteem variable (X1) partially influences the organizational commitment variable (Y). For the work ethic variable (X2), the value obtained is tcount 4.570 > ttable 1.987, meaning that the work ethic variable (X2) partially influences the organizational commitment variable (Y).